Dynamic range expansion of a Shack-Hartmann sensor by use of a modified unwrapping algorithm - Lindlein, Norbert; et al. (Optics Letters, 1998)
An algorithm for expanding the dynamic range of Shack-Hartmann sensors is proposed. The distribution of the spot dislocations is treated with a modified unwrapping algorithm that is widely used in interferometry. The algorithm unwraps the spot dislocations and assigns the spots to their original subapertures, leading to a huge expansion of the dynamic range. For the proposed algorithm there remains a limitation on the maximum wave-front curvature instead of on the maximum wave-front slope. Examples are given that show spot fields that were wrapped four times; the measured wave front had a peak-to-valley value of 116λ. © 1998 Optical Society of America.
UnivIS-Import:2015-03-05:Pub.1998.nat.dphy.optik.1optik.dynami